Developing a composite-based constitutive model for municipal solid waste - M.R. Yousefi; A. Noorzad; M.J. Mahmoodi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Harmful ruptures and instabilities in landfills in recent years have highlighted the importance of studying the municipal solid waste and its behavior. These instabilities mostly occur in the landfill of developing countries where waste materials are degradable and saturated. The behavior of waste and its ingredients are unknown as the main reasons for such instability. The main goal of this study was to better predict the behavior of landfills and unknown materials in municipal solid waste to prevent the environmental disasters.METHODS: A cylindrical specimen was modeled and subjected to triaxial test loading conditions using the finite element method. Also, fresh waste, as a waste sample with a specific composition, was investigated. Using the optimization method, the constants of the presented equation were obtained and the basic model of stress strain was presented based on composite theory.FINDINGS: The whole models for predicting the waste behavior were presented based on the behavior models of soils. This was carried out by the theory of composite materials, which was used for the first time in this study. At the strains of less than 30 percent, a well agreement was observed between the results of the numerical and the present methods. Also, at confining stresses less than 100 kiloPascal, the root mean square of the relative error percentages between the total stresses obtained from the present model and another model was less than 10 percent. At higher confining stresses, this amount was in the range of 10 – 20 percent.CONCLUSION: The results of this study were compared with those of the experimental data in previous models to verify the proposed model. The model proved to be capable of simulating and predicting the municipal solid waste behavior under various loading conditions efficiently. The results implied that assuming the municipal solid waste as composite material was reasonable and could be extended to future studies.